PENGARUH FASILITAS TERHADAP KEPUTUSAN MENGINAP DI GRAND ROCKY HOTEL BUKITTINGGI - Gabrylia Gema Balinda; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Grand Rocky Hotel Bukittinggi is one of the 4-star hotels in the Bukittinggi. High competition and ups and downs of occupancy rates in the last 4 years makes the company must have a strategy to maintain the occupancy of consumers so that each year purchasing decisions increase. This research was conducted to determine the effect of facilities on consumer purchasing decisions. This study uses a quantitative method with a statistical approach. Data obtained from 100 respondents who stayed at the Grand Rocky Hotel Bukittinggi. Then the data obtained were analyzed using multiple regression analysis: validity and reliability tests, classic assumption tests, multiple regression analysis, hypothesis testing through t and F tests, and analysis of the coefficient of determination (R2). An adjusted R square value of 0.505 indicates that the facility affects the stay decision by 50.5 percent. Keywords: Facilities, Stay Decisions, Hotels